Applications of field-programmable gate arrays in scientific research - Sadrozinski, H. F.-W. (Hartmut F.-W.); Wu, Jinyuan (Boca Raton, FL : CRC Press, 2010)
'Emphasizing concepts and practical examples, this book presents an introduction to applications of field-programmable gate arrays (FPGAs) in various fields of research. Examining the principle of FPGAs and their functionality, the book explores how FPGAs work and how they are programmed to specific areas of applications in physics. Many figures and hands-on examples are included to show why FPGAs are so popular. The book also contains several chapters on special topics contributed by experts in the field, with information on applications in radiobiology, large-scale data management, HEP, nuclear physics, and photon science'--
Includes bibliographical references and index.
Keywords: Scientific apparatus and instruments; Field programmable gate arrays -- Scientific applications; COMPUTERS / Microprocessors; SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Electronics / Microelectronics